2024
DOI: 10.1108/ijis-03-2023-0071
|View full text |Cite
|
Sign up to set email alerts
|

Convexity of the triple helix of innovation game

Eustache Mêgnigbêto

Abstract: Purpose This paper aims to determine the conditions for the core of the Triple Helix game to exist. The Triple Helix of university-industry-government relationships is a three-person cooperative game with transferable utility. Then, the core, the Shapley value and the nucleolus were used as indicators of the synergy within an innovation system. Whereas the Shapley value and the nucleolus always exist, the core may not. Design/methodology/approach The core of a three-person cooperative game with transferable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Thirdly, Shapley (1965Shapley ( , 1971) stated that a convex game is decomposable (therefore, may split into its finest components) and demonstrated that a strictly convex game is indecomposable (see also González-Díaz & Sánchez-Rodríguez, 2008). Because a Triple Helix game where all the bilateral and the trilateral relationships exist is strictly convex (cf., Mêgnigbêto, 2024), it is indecomposable. In conclusion, neither the global Triple Helix game is the summation or the combination of the domestic and foreign Triple Helix games, nor the Triple Helix domestic and foreign games are components of the global Triple Helix game.…”
Section: Triple Helix Relationships Constituted Of Two Layersmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirdly, Shapley (1965Shapley ( , 1971) stated that a convex game is decomposable (therefore, may split into its finest components) and demonstrated that a strictly convex game is indecomposable (see also González-Díaz & Sánchez-Rodríguez, 2008). Because a Triple Helix game where all the bilateral and the trilateral relationships exist is strictly convex (cf., Mêgnigbêto, 2024), it is indecomposable. In conclusion, neither the global Triple Helix game is the summation or the combination of the domestic and foreign Triple Helix games, nor the Triple Helix domestic and foreign games are components of the global Triple Helix game.…”
Section: Triple Helix Relationships Constituted Of Two Layersmentioning
confidence: 99%
“…Let us individually consider each layer (its actors and their collaboration relations at the level): it is an entire Triple Helix relationship, so a game (Mêgnigbêto, 2018c); hence, the Triple Helix game at an area level may be analyzed as bringing together two games, the domestic and the foreign one, with the same actors (university, industry and government) that may play either at the domestic or at the foreign level. Mêgnigbêto (2024) showed that a Triple Helix of innovators game is convex; therefore, the global, domestic, and foreign (above-mentioned) games all are convex.…”
Section: Triple Helix Relationships Constituted Of Two Layersmentioning
confidence: 99%
See 2 more Smart Citations